ΑΝΑΔΡΟΜΗ ΣΤΗΝ ΕΡΕΥΝΑ ΓΙΑ ΤΟ ΘΕΑΤΡΟ ΤΟΥ ΔΗΜΗΤΡΗ ΔΗΜΗΤΡΙΑΔΗ ΜΕ ΑΦΟΡΜΗ ΤΗ ΜΕΛΕΤΗ-ΣΤΑΘΜΟ ΤΟΥ ΒΑΛΤΕΡ ΠΟΥΧΝΕΡ [REVISITING THE CRITICAL RESEARCH INTO DIMITRIS DIMITRIADIS’ THEATRICAL WORK ON THE OCCASION OF WALTER PUCHNER’S MONUMENTAL STUDY] - Kondylaki, Dimitra (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
This article seeks to foreground the scholarly merits of Walter Puchner’s published study The Theatre of Dimitris Dimitriadis: An Essay on Theatrical Postmodernism (Nefeli Publishing, «Theatre: Art—Society—Politics» series, 2023, 620 pages), by offering a brief yet concise retrospective of the research conducted on the Greek dramaturg’s theatrical work—whom Puchner sketches as «the most prolific figure in contemporary literary and theatrical history, second only to Iakovos Kambanellis». As a culmination of the critical research into Dimitriadis’ work since the 1990s, Puchner’s volume definitively dispels the long-standing perception of the dramaturg as an “outsider,” firmly establishing him as a leading playwright. In doing so, it provides a comprehensive account of his body of theatre work, encompassing more than sixty published plays as well as a significant number of unpublished texts, extending through to 2019.